ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI KELAYAKAN USAHA HOME INDUSTRI TAHU DI DESA RAMBAH MUDA (DI TINJAU DARI ASPEK PRODUKSI DAN ASPEK KEUANGAN) - Siti Aisyah Sabri; Andi Afrizal; Arrafiqur Rahman (Strata Business Review, 2025)
The tofu industry in Rambah Muda Village is a home based business that processes soybeans into tofu products. Despite its potential, the industry faces several operational challenges, including rising raw material prices, production failures, limited market reach, and high competition. This study aims to analyze the feasibility of tofu businesses in Rambah Muda Village from technical production and financial perspectives. A qualitative descriptive method was employed, using data collected through field observations, interviews, and documentation. The technical production analysis focused on aspects such as business location, equipment, raw materials, labor, and production layout. Financial feasibility was assessed using Payback Period (PP), Net Present Value (NPV), and Break Even Point (BEP) indicators. The findings indicate that (1) from a technical and production standpoint, the tofu businesses operated by Mbah Warijan and Mama Gibran are feasible and have the necessary infrastructure to continue operations and (2) from a financial perspective, both businesses demonstrate positive results across all indicators, suggesting long term viability. The study recommends further development through marketing strategies and technological improvement to enhance competitiveness.